Distanciamiento de siembra y su influencia en las características agronómicas y su rendimiento de Solanum melongena L. “berenjena”, Zungarococha - Loreto. 2019 - Ramirez Olortegui, Carol Vanessa (2022)
The thesis was developed in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the road to Zungarococha, south of the city of Iquitos, whose coordinates in UTM are: 9576237 North and 682157 South and Altitude: 126 meters above sea level. The type of research was experimental, explanatory, prospective, longitudinal and prospective, with an independent variable: Planting distance, whose treatments were as follows: 1.50 m x 0.70 m (T1); 1 m x 0.70 m (T2); 1.3 m x 0.70 m (T3) and 1.8 m x 0.70 m (T4). and eight dependent variables (plant height, plant diameter, fruit length, fruit diameter, fruit weight, fruit/plant number, fruit/plant weight, fruit/ha weight. The objective of the research work was to determine the influence of planting estating on the agronomic characteristics and yield of Solanum melongena L. "berenjena", Zungarococha-Loreto. 2019. The experimental design used was Completely Random Block Design, with four treatments and four repetitions. At the end of the experiment it is concluded that, planting estating influences the agronomic characteristics and yield of Solanum melongena L. "berenjena", the T4 Treatment (1.8 m x 0.7 m), I present the best agronomic characteristics of the plant diameter, the length and diameter of the fruit, the T3 (1.3 m x 0.7 m), presented the best plant height; the T4 Treatment (1.8 m x 0.7 m), presented the best average values of fruit weight and fruit/plant weight, with 228 g and 1824 g respectively; the T2 Treatment (1 m x 0.7 m), I present the highest average values of number of fruits/plant, weight of fruits/ha, with 10 fruits and 17,243 t/ha respectively, treatment T2 (1 m x 0.7 m), had the best benefit-to-cost ratio, with a return of S/.57,640.00.